Trade-Off Between Growth Regimes in Chlorella vulgaris: Impact on Carotenoid Production - Patrícia Acosta Caetano; Pricila Pinheiro Nass; Mariany Costa Deprá; Tatiele Casagrande do Nascimento; Eduardo Jacob-Lopes; Leila Queiroz Zepka (Colorants)
With the increasing awareness of socio-environmental issues, a global trend has emerged emphasizing the valorization of natural ingredients that promote health and well-being within sustainable production systems, such as microalgae-based carotenoids. Currently, little is understood about the correlation between biomass productivity and carotenoid content, which is a fundamental parameter for facilitating the immediate expansion of microalgae bioprocesses and ensuring the availability and industrial viability of these compounds. In this context, this study aims to investigate the carotenoid profile of Chlorella vulgaris through growth curve experiments conducted under photoautotrophic and heterotrophic regimes. Additionally, a trade-off analysis was performed for the production of carotenoids from microalgae. Carotenoids were quantified using high-performance liquid chromatography coupled with diode array and mass spectrometry detectors (HPLC-PDA-MS/MS). The performance of kinetic phases and energy demands across growth regimes was assessed to provide insights into production trade-offs. The results indicated that a total of 22 different carotenoids were identified in all the extracts. The all-trans-lutein and all-trans-β-carotene were the majority compounds. The total carotenoid content of Chlorella vulgaris revealed significant differences in the kinetic phases of carotenoid production, indicating that carotenoid volumetric production is only viable if the cultures are conducted until the log and stationary phases, based on the function of the biomass volumetric production (weight.volume−1). Therefore, the best trade-off for the process was to provide photoautotrophic growth until the exponential phase (log). Under this condition, the maximum carotenoid and lutein content was 2921.70 µg.L−1, reaching a maximum cell biomass of 1.46 g.L−1. From an environmental/economic point of view, the energy demand was 7.74 kWh.L−1. Finally, the scientific advances achieved in this study provide a holistic view of the influence of the main cultivation methods on the production of microalgae carotenoids, suggesting a viable initial direction for different industrial applications.